A global meta‐analysis of exotic versus native leaf decay in stream ecosystems. (31st March 2017) - Kennedy, Kimberly T. M.; El‐Sabaawi, Rana W.
Abstract: Streams are reliant on streamside plants for allochthonous inputs that form the base of the stream food web. The impact of exotic leaves on stream ecosystems has been investigated regionally, but not assessed globally. In this study, we conducted a global meta‐analysis contrasting native and exotic aquatic litter decay. We used a linear mixed effects model to identify how the site‐specific factors and experimental treatments of latitude, temperature, pH, conductivity and the exclusion of invertebrates (via mesh size) cause relative differences in exotic and native decay rates. Subsequently, we assessed whether differences in native and exotic litter decay rates were driven by the intrinsic factors of leaf litter quality. We found that overall leaf litter decay rates were similar for native and exotic leaves on a global scale. However, we also found that exotic leaves decayed faster than native leaves at higher stream temperatures and in larger mesh sizes (allowing macroinvertebrate access); yet, those differences disappeared at lower temperatures and in finer mesh sizes which excluded macroinvertebrates. Post hoc analysis of leaf quality suggested that differences between higher native and lower exotic leaf C:N ratios might explain differences in decomposition rates observed at high temperature, and differences between lower native and higher exotic leaf C:P ratios associated with differences in decomposition rates observed at coarse mesh sizes. Our study suggests that exotic leaf litter is likely to have the most impact in high‐temperature stream ecosystems and that the nature of the impact is potentially related to the C:N ratio differences between native and exotic leaves. This might indicate that higher temperature stream ecosystems are more vulnerable to changes in litter decay rates due to invasion by exotic plant species than lower temperature stream ecosystems, and should be monitored accordingly. We recommend that future leaf litter decay studies include stream discharge measurements and leaf litter quality information so that both intrinsic and extrinsic factors that impact litter decay can be fully accounted for when assessing the factors that drive differences in leaf litter decay rates.